2016
DOI: 10.1017/s0007114516000179
|View full text |Cite
|
Sign up to set email alerts
|

The influence of BMI on the association between serum lycopene and the metabolic syndrome

Abstract: Overweight and obese individuals have an increased risk of developing the metabolic syndrome because of subsequent chronic inflammation and oxidative stress, which the antioxidant nutrient lycopene can reduce. However, studies indicate that different BMI statuses can alter the positive effects of lycopene. Therefore, the purpose of this study was to examine how BMI influences the association between serum lycopene and the metabolic syndrome. The tertile rank method was used to divide 13 196 participants, aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 37 publications
2
16
0
2
Order By: Relevance
“…The risk of metabolic syndrome increased by 2.14 times at ages of 65 years. Similar results were observed by Park et al [9], who reported that the risk was 5.62 times higher at the ages of 60e69 years than at the ages of 20e29 years, and Han et al [22], who reported that the risk was 6.07 times higher at the ages of 60 years than at the ages of 20e39 years. Age-related increases in abdominal obesity and blood pressure appear to significantly influence the prevalence of metabolic syndrome [5].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The risk of metabolic syndrome increased by 2.14 times at ages of 65 years. Similar results were observed by Park et al [9], who reported that the risk was 5.62 times higher at the ages of 60e69 years than at the ages of 20e29 years, and Han et al [22], who reported that the risk was 6.07 times higher at the ages of 60 years than at the ages of 20e39 years. Age-related increases in abdominal obesity and blood pressure appear to significantly influence the prevalence of metabolic syndrome [5].…”
Section: Discussionsupporting
confidence: 87%
“…Among disabled persons, BMI was the most significant factor influencing metabolic syndrome, with a 4.67 times higher risk of metabolic syndrome for obese persons than for normal weight persons. Similarly, Park et al [9] reported that the risk of metabolic syndrome is 14.08 times higher for obese persons, and Han et al [22] reported that the risk of metabolic syndrome is 20.35 times higher for obese persons than for normal weight persons. Furthermore, 67.1% of disabled persons with metabolic syndrome are obese, and the risk of metabolic syndrome increased sharply in the obese group, which highlights the importance of weight control in preventing and managing metabolic syndrome.…”
Section: Discussionmentioning
confidence: 91%
“…The main biological mechanism by which lycopene reduces the risk and mortality of the metabolic syndrome , include the antioxidant, anti-inflammatory and antiobesity effects, the ability to improve endothelial function, glycemic control, insulin sensitivity and lipid profile (Tsitsimpikou et al, 2014 ; Li et al, 2015 ; Han et al, 2016a , b ). An inverse relationship was found by Yeo et al between lycopene level and brachial-ankle pulse wave velocity (Yeo et al, 2011 ).…”
Section: Clinical Researchmentioning
confidence: 99%
“…Higher serum carotenoid levels were associated not just with a lower prevalence of the metabolic syndrome, but also with fewer abnormal metabolic syndrome components. A significant association between lycopene and the metabolic syndrome was described only for normal-weight and overweight participants, but not in obese patients, according to a study enrolling 13,196 subjects, probably related to an increased oxidative stress and decreased antioxidant ability, due to sequestration of lycopene in the adipose tissue and more important inflammation in obese (Han et al, 2016b ). On the other hand, daily tomato juice intake reduced waist circumference, cholesterol, and monocyte chemotactic protein-1 (inflammatory adipokine) and increased adiponectin (anti-inflammatory adipokine) levels in 30 young, healthy Taiwanese females (Li et al, 2015 ).…”
Section: Clinical Researchmentioning
confidence: 99%
“…The NHANES study that enrolled 13 196 adults (≥20 years of age) found that higher serum concentrations of lycopene are associated with reduced MetS prevalence, but only in participants with normal weight or overweight, and not in those with obesity [ 3 ]. Among the 2499 participants with MetS, higher serum lycopene concentration was associated with longer survival [ 4 ].…”
Section: Carotenoids and Vitamin Amentioning
confidence: 99%